Parametric Study of Double Axes Tracking Heliostat to Optimize Heliostat Field Efficiency - Nor Shaharim, Mohammad Haqimi Izwan (IRC, 2020)
The paper presents the research on optimization of heliostat field in terms of distance of heliostat relative to the receiver. The heliostat field consist of sun tracking mirror (heliostat) that reflects the sun radiation to the receiver at the top of the tower. Heliostat field efficiency is related to cosine loss and atmospheric attenuation loss. Increasing the distance of heliostat relative to the receiver, results in higher cosine loss and atmospheric loss. The heliostat field is located in Ipoh, Malaysia (latitudea4.340aN). The angle of incidence is calculated using sun position and heliostat position related equations that had been established in the mathematical model.